Pratiques citoyennes de pères québécois: contribution aux recherches entreprises par Éric Schwimmer - Campeau, André (Anthropologica, 2022)
The thesis put forth by Schwimmer (2001) in connection with citizenship makes it possible to show that, under current conditions, the Canadian state imposes conditions on Quebec. This thesis constitutes a baseline from which it is possible to conceive of a mediation (citizenship) between these two socio-political realities which are, on the one hand, the Canadian regime generating policies and public actions and, on the other hand, a nation whose history is characterized by minoritization. While referring to two sites traversed by the question of Quebecois fatherhood, the author proposes Schwimmer’s thesis (2001) as an analytical framework of practices of citizenship juxtaposed to state order and the nation via mediation which is different in Quebec and Canada. This view emphasizes that citizen practices of mediation are not possible when the question raised is marginalized by one of the parties and when the other party does not have all the resources to work out its own discourse—in other words, to build citizenship collectively.